In vitro conversion of saturated to monounsaturated fatty acid by Ehrlich ascites cells - Mercuri, Osvaldo Francisco (1981)
In this paper, evidence is presented on the capacity of Ehrlich ascites cells to synthesize in vitro monounsaturated fatty acids from radioactive palmitate. Localization of the double bond was determined by ozonolysis and subsequent reduction of the ozonides to aldesters followed by gas liquid chromatography. These results proved that Ehrlich ascites cells have a Δ9 desaturase that catalyzes the biosynthesis of palmitoleic acid from palmitic acid and oleic and vaccenic acid via elongation-desaturation and desaturation-elongation, respectively, using palmitic acid as substrate. Furthermore, it is shown that, as in the hepatic cells, Δ9 desaturase enzyme activity of the tumoral cells is associated with the endoplasmic reticulum. The electron transport components involved in the desaturase system, i.e., NADH-cytochrome bs reductase and NADH-cytochrome bs reductase, were also measured. The activities of these enzymes do not appear to be rate-limiting in the desaturase activity of these tumoral cells.